Content Analysis as a Method to Assess Online Discussions for Learning. (28th November 2014) - Rodriguez, Mark A.
One of the challenges for instructors in online education is to create learning opportunities through online text-based discourse. The goal of this study was to examine the use of content analysis to better understand graduate students' learning in online discussions. The discussion transcripts of a hybrid graduate course were analyzed to determine levels and frequencies of learning or cognitive presence. The analysis of the online discussions was guided by social constructivist rationale, and includes descriptive statistics and inter-rater reliability measurements. Findings show that cognitive presence levels were concentrated in categories marked for exploration and integration. Non-cognitive messages resulted in the highest frequencies of discussion messages, demonstrating indications of social presence and teaching presence. Training was found to be a key factor in resolving coding inconsistencies to improve the reliability of the content analysis. The processes of content analysis applied in this study to evaluate learning in online discussions provided useful information for the development and study of online discussions for learning.